2013
DOI: 10.4321/s1886-36552013000200003
|View full text |Cite
|
Sign up to set email alerts
|

Associations of gender and age groups on the knowledge and use of drug information resources by American pharmacists

Abstract: *Objectives: To explore knowledge and use of drug information resources by pharmacists and identify patterns influenced by gender and age-group classification. Methods: A survey questionnaire was mailed nationwide to 1,000 practitioners working in community (n = 500) and hospital (n = 500) settings who answer drug information questions as part of their expected job responsibilities. Responses pertaining to drug information resource use and knowledge of different types of drug-related queries, resource media pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 36 publications
0
16
0
Order By: Relevance
“…Third, electronic survey respondents may not be representative of the general population. Pharmacists who prefer electronic media tend to be younger, 26 …”
Section: A N U S C R I P Tmentioning
confidence: 99%
“…Third, electronic survey respondents may not be representative of the general population. Pharmacists who prefer electronic media tend to be younger, 26 …”
Section: A N U S C R I P Tmentioning
confidence: 99%
“…8 A survey questionnaire conducted by Carvajal et al showed that 70% of pharmacists, in both hospital and community settings, responded that the drug information resource most frequently used in their pharmacy was electronic. 9 This finding supported the commonly held platitude that, since technology is rapidly advancing and electronic resources offer timely and readily accessible information, they are increasingly being substituted for print resources. 8 Electronic resources expedite information gathering and decision-making, which can improve patient care.…”
Section: Introductionmentioning
confidence: 57%
“…Currently, the optimal method of formatting ADR information in DI databases is unknown, and there is no professional guidance in this area. Other studies that have evaluated user preference for DI databases have generated mixed results [10,24].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, it is known that a substantial proportion of DI questions posed in practice deal with potential ADRs. By responding to such queries, pharmacists and other clinicians can add value to pharmacovigilance in health care settings [ 8 , 22 – 24 ].…”
Section: Discussionmentioning
confidence: 99%